2008
DOI: 10.1249/mss.0b013e31817c92aa
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Physical Activity Level, Telomere Length, and Telomerase Activity

Abstract: Purpose-The purpose of this study was to examine the relationship of exercise energy expenditure (EEE) with both telomere length and telomerase activity in addition to accounting for hTERT C-1327T promoter genotype.Methods-Sixty-nine (n = 34 males; n = 35 females) participants 50-70 yr were assessed for weekly EEE level using the Yale Physical Activity Survey. Lifetime consistency of EEE was also determined. Subjects were recruited across a large range of EEE levels and separated into quartiles: 0-990, 991-234… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
197
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(215 citation statements)
references
References 31 publications
11
197
2
5
Order By: Relevance
“…This trend toward longer telomeres was detected not only in the whole CD4 + and CD8 + T cell compartments but also in their respective CD45RO + /CD45RO neg and CD28 + /CD28 neg subsets, although statistical significance was observed only in the total CD8 + and CD8 + CD28 neg compartments between the IT and NT groups. These data are particularly important because previous studies on telomere length and physical activity showed conflicting results (Cherkas et al 2008;Ludlow et al 2008;Shin et al 2008;Woo et al 2008;Du et al 2012;Laine et al 2015). Comparisons among these studies are limited by differences in study design, including the immunological parameters assessed and the cohorts analyzed, which differed not only in age and gender but also in the type, intensity, and regularity of physical activity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This trend toward longer telomeres was detected not only in the whole CD4 + and CD8 + T cell compartments but also in their respective CD45RO + /CD45RO neg and CD28 + /CD28 neg subsets, although statistical significance was observed only in the total CD8 + and CD8 + CD28 neg compartments between the IT and NT groups. These data are particularly important because previous studies on telomere length and physical activity showed conflicting results (Cherkas et al 2008;Ludlow et al 2008;Shin et al 2008;Woo et al 2008;Du et al 2012;Laine et al 2015). Comparisons among these studies are limited by differences in study design, including the immunological parameters assessed and the cohorts analyzed, which differed not only in age and gender but also in the type, intensity, and regularity of physical activity.…”
Section: Discussionmentioning
confidence: 95%
“…Telomere shortening has been considered a marker of immunosenescence. The impact of regular exercise on telomere length remains controversial, with studies showing either no effect (Shin et al 2008;Woo et al 2008;Laine et al 2015) or a protective effect (Cherkas et al 2008;Ludlow et al 2008;Du et al 2012). Therefore, we measured and compared telomere length in total T cells [CD3 + ], CD4 + CD45RO + T cells, CD4 + CD45RO neg T cells, CD8 + CD28 + T cells, and CD8 + CD28 neg T cells among the groups.…”
Section: Telomere Lengthmentioning
confidence: 99%
“…Many studies have, however, either failed to confirm this association (Harris et al 2006b;Cassidy et al 2010) or reported an inverted U-curve association in which telomeres were longest in participants who were moderately active and shortest among those who were inactive or very active (Ludlow et al 2008). Very few of the participants in this study were physically very active; thus, conclusions on whether faster telomere erosion is related to a high level of physical activity cannot be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be considered that TL in different cell types may better reflect specific diseases, tissue-specific aging, or cell-specific adaptations [67]. To Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/redox date, there are many evidences about the association between habitual PA and longer leukocyte telomere length (LTL) [14,17,37,40,71,18,57,39], but most of them derive from studies where aerobic endurance-exercise training was used as intervention [14,17,37,18,57]. Moreover, they have shown conflicting results, with telomeres that can take three different trajectories (expected shortening, maintenance, and lengthening).…”
Section: Introductionmentioning
confidence: 99%